2007
DOI: 10.17660/actahortic.2007.748.28
|View full text |Cite
|
Sign up to set email alerts
|

First Data From a Field Trial of Quercus Suber Plants Regenerated From Mature Selected Trees and From Their Half-Sib Progenies by Somatic Embryogenesis

Abstract: The development of reliable clonal propagation technologies is a requisite for performing Multi-Varietal Forestry (MVF). Somatic embryogenesis is considered the tissue culture based method more suitable for operational breeding of forest trees. Vegetative propagation is very difficult when tissues are taken from mature donors, making clonal propagation of selected trees almost impossible. We have been able to induce somatic embryogenesis in leaves taken from mature oak trees, including cork oak (Quercus suber)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Differences as a result of genotype and family effects were notable and no apparent morphological alterations were detected among the trees of tested progenies (Celestino et al 2007). …”
Section: Maturation Germination and Plantlet Conversionmentioning
confidence: 90%
“…Differences as a result of genotype and family effects were notable and no apparent morphological alterations were detected among the trees of tested progenies (Celestino et al 2007). …”
Section: Maturation Germination and Plantlet Conversionmentioning
confidence: 90%
“…As well, an influence of the different mean root number produced by these plantlets in vitro (Table 2) could also cause this difference, especially during the first period of growth after transplanting. In contrast, no differences were found between cork oak somatic plants of adult (epicormic shoots) and juvenile (seedlings from halfsib acorns of the adult trees) origin after the first growing season in the field (Celestino et al 2007). However, apart from a possible genotypic effect, a different experimental model was used in cork oak in which plants were derived from germinated somatic embryos, whereas in this study somatic embryo-derived clones and rooted plants were used.…”
Section: Discussionmentioning
confidence: 82%
“…Higher numbers of globular-, heart-, torpedo-, and cotyledon-stage somatic embryos were then obtained after culture on medium devoid of 2,4-D, with germination and development of plants after desiccation and cold storage. In vitro studies on Q. suber embryogenesis and diploidization of antherderived embryos (for breeding purposes) continues to advance the improvement, conservation, and production of this important forest and agro-forestry species (high-quality cork; acorns for feed for cattle and pig farming; Celestino et al 2007Celestino et al , 2009Pintos et al 2007Pintos et al , 2008Gomez et al 2009). Anther-derived haploid embryos from six genotypes were treated with three different anti-mitotic agents, and 0.01 mM oryzalin (for 48 h) produced approximately 50% diploid embryos (Pintos et al 2007).…”
Section: Conservation Through In Vitro Technologiesmentioning
confidence: 99%
“…Pintos et al (2008) encapsulated somatic embryos of cork oak for the production and storage (4°C for 2 mo without significant loss) of synthetic seeds, and monitored the growth with a digital image system. Celestino et al (2007Celestino et al ( , 2009 and Pintos et al (2009) reported on field trials of cork oak plants regenerated via somatic embryogenesis, and they concluded that the regenerated plants showed a cork quality trait similar to that of the parent tree. Proteomic analysis of haploid and diploid embryos of cork oak identified 17 differentially expressed proteins; of which some were involved in the synthesis of cork chemical components (Gomez et al 2009).…”
Section: Conservation Through In Vitro Technologiesmentioning
confidence: 99%